Respon Pemerintah Kalurahan Sumbermulyo terhadap Kebijakan Penanggulangan COVID-19 - Krisjuyani, Susi (Universitas Kapuas Sintang, 2024)
A response is an answer or reaction to an action, event, or situation that occurs. Influenced by applicable policies and regulations. And it is very important to do this, because if you do not respond to policies it will cause problems, namely weakening the effectiveness of those who make and implement policies, reduce trust and damage social and legal order. Researchers are interested in answering this problem by trying to answer the problem formulation: How has the Sumbermulyo District Government responded to the COVID-19 Management Policy? The aim of this research is to describe or illustrate existing phenomena and the facts that occur. So the method used is a qualitative research method with a narrative approach. The object of this research is the Response of the Sumbermulyo District Government to the COVID-19 Management Policy. The informants for this research were the Village Head, Village Secretary, Hamlet Head, Community Elements, and Sumbermulyo Village Community Protection Unit Officers. The Sumbermulyo Village Government's response to the COVID-19 Management Policy is as a follow-up to the policy made by the Government. The Sumbermulyo Village Government is following the orders given by the supravillage Government. The Sumbermulyo District Government in responding to COVID-19 formed Village volunteers to fight COVID-19 starting from the Village Headquarters down to the Padukuhan level, through Village Head Decree and Village Regulations, spraying disinfectant in all Padukuhan, forming Village quarantine houses, Handling using Village Funds and making changes to APBDes. Therefore, the researcher provides advice: In responding to policies, you must look at the capabilities of the sub-district and the condition of the community, not just follow orders. In handling it, you should not only focus on using Village Funds, but also utilize other financial sources, such as ADD, PADes, and other legitimate assistance.